The millennial generation and wine purchasing beliefs in casual dining restaurants - Thompson, Kelly R. (Kansas State University, 2010)
The primary purposes of this research were to 1) use the Theory of Planned Behavior (TPB)to assess Millennial generation wine consumers attitudes, perceived behavioral controls, and subjective norms related to purchasing wine in casual dining restaurants (CDR), and 2) use Conjoint Analysis (CA) to analyze Millennials’ preferences for wine information on the restaurant menu. An instrument was designed based on the TPB and CA and was sent online to 216 consumers using the database of a market research firm (e-rewards). Independent variables (attitude, perceived behavioral control, and subjective norms) were analyzed to predict behavioral intentions to purchase wine. Principal component analysis was combined with multiple linear regression to assess intention. Results identified attitudes and subjective norms as being significant in predicting behavioral intention, perceived behavioral controls was partially significant. Millennial’s believe ordering wine with their friends and family in casual dining restaurants will make them feel smart and sophisticated and will increase the enjoyment of food. However, they do not believe wine consumption is appropriate in CDR’s; they had strong perceptions that wine is purchased for special occasions and consumed in fine dining restaurants. Part II of the study employed conjoint analysis to determine Millennials preferences for wine information on the menu. Results indicated that Millennials prefer menus that provide wine/food pairing information, wine flavor descriptors located near food listings and quality wines at an affordable price. Millennials attitudes, subjective norms, and perceived behavioral controls support previous research that this generation is interested in wine and wine is a social experience that increases their enjoyment of food and time spent with their friends and family. Through the use of CA, the present study suggests wine information on the menu is important to this segment of consumers. Additional research should be conducted to understand the stereotypes this generation has about wine consumption in casual dining restaurants. These operators and owners should consider focusing their marketing efforts showing Millennials enjoying wine while celebrating special occasions with their friends and family. In addition, redeveloping menus in their operations to add wine information may increase interest in wine and generate profit.
Keywords: Millennials; Theory of Planned Behavior (TPB); Conjoint analysis (CA); Wine; Purchasing; Casual dining; Agriculture, Food Science and Technology (0359); Business Administration, Marketing (0338)